A Review of Mesoporous Silica Nanoparticle Delivery Systems in Chemo-Based Combination Cancer Therapies - Gao, Ying; Gao, Dongruo; Shen, Jie; Wang, Qiwen (Frontiers in Chemistry, 2020)
Chemotherapy is an important anti-tumor treatment in clinic to date, however, the effectiveness of traditional chemotherapy is limited by its poor selectivity, high systemic toxicity, and multidrug resistance. In recent years, mesoporous silica nanoparticles (MSNs) have become exciting drug delivery systems (DDS) due to their unique advantages, such as easy large-scale production, adjustable uniform pore size, large surface area and pore volumes. While mesoporous silica-based DDS can improve chemotherapy to a certain extent, when used in combination with other cancer therapies MSN based chemotherapy exhibits a synergistic effect, greatly improving therapeutic outcomes. In this review, we discuss the applications of MSN DDS for a diverse range of chemotherapeutic combination anti-tumor therapies, including phototherapy, gene therapy, immunotherapy and other less common modalities. Furthermore, we focus on the characteristics of each nanomaterial and the synergistic advantages of the combination therapies. Lastly, we examine the challenges and future prospects of MSN based chemotherapeutic combination therapies.